Correction: Iron-promoted free radical cascade difunctionalization of unsaturated benzamides with silanes. Issue 58 (8th July 2022) - Ge, Yaxin; Tian, Yunfei; Wu, Jilai; Yan, Qinqin; Zheng, Luping; Ren, Yingming; Zhao, Jincan; Li, Zejiang
Abstract : Correction for 'Iron-promoted free radical cascade difunctionalization of unsaturated benzamides with silanes' by Yaxin Ge et al., Chem. Commun., 2020, 56, 12656–12659, ; https://doi.org/10.1039/D0CC05213B .